Are trade openness drivers relevant to carbon dioxide emission? a study of emerging economies - Suleman, Shahida; Boukhris, Mohamed; Kayani, Umar Nawaz; Mohd Thas Thaker, Hassanudin; Cheong, Calvin W. H; Hadili, Abduraawf; Tehseen, Shehnaz (EconJournals, 2024)
This research is focused on an in-depth analysis of the trade drivers that influence trade openness and their impact on carbon dioxide emissions, with a concentrated examination of emerging economies from 1995 to 2020. This examination is contextualized within the scope of various trade and environmental theoretical frameworks. In our analysis, we employed a range of advanced panel regression methods, including stepwise regression for model selection, as well as Fully Modified Ordinary Least Squares (FMOLS), Panel Ordinary Least Squares (Panel OLS), and Fixed Effects Model (FEM). The long-term patterns were evaluated using Johansen co-integration tests. Additionally, the study delves into the causal links between carbon dioxide emissions and the key drivers of trade, employing Granger causality tests for this purpose. Our findings disclose a complex web of relationships, both in the short and long term, between trade openness and carbon dioxide emissions, influenced by several key factors: (i) net inflows of foreign direct investment, (ii) trade reserves, (iii) per capita income, (iv) exchange rates, and (v) gross national savings.